Ethical Guidance for Neuroprognostication in Disorders of Consciousness. (26th April 2022) - Paretsky, Melissa Shuman; Albert, Steven; Giacino, Joseph T.
Abstract : In the United States, 4.8 million individuals present to the emergency department for traumatic brain injury (TBI) evaluation and 2.9 million are diagnosed with TBI every year. Approximately 224, 000 are hospitalized due to injury severity. 1 Recent studies have demonstrated variability and conflicts in decision-making surrounding withdrawal or limitation of care (WLC). One study that looked at a decade of deaths (54% related to WLC) at a level 1 trauma center in the United States found decision-making conflicts between physicians and family (57%), between family members (33%), and between patients and family members (9.5%). 2 Although 68% of WLC cases were from a similar US level 1 trauma treatment center study, there were differences in TBI severity (64% for severe TBI and 92% for moderate TBI) and both within-center and between-center variation in decision-making. 3 Finally, although about 70% of deaths were associated with WLC in a 2-year retrospective cohort study at 6 Canadian level 1 trauma centers, there was variability between treatment centers (45%–87%). 4 These studies demonstrate an international trend for variability in treatment and conflicts in decision-making regarding WLC for patients with disorders of consciousness (DoC).